A Case of Angiomyolipoma Rarely Located in the Larynx. (9th October 2011) - Eyigor, Hulya; Suren, Dinc; Osma, Ustun; Sezer, Cem; Yilmaz, Mustafa Deniz
Abstract : Angiomyolipoma is a rare benign mesenchymal tumor, which is mostly renal in origin. A sixty-year-old male patient with the diagnosis of angiomyolipoma located in the larynx has been presented here, and the literature is reviewed